The Influence of Educational Administration on Improving the Quality and Quality of Education at MIS Hanif Al Fikri Schools - Aziz, Mursal; Harahap, M. Abrar Putra Kaya; Megarani, Omega; Syakira Ridwan, Fitri (JUPE : Jurnal Pendidikan Mandala, 2024)
To support adequate education and of course of good quality, it is necessary to carry out various series of programs. The educational programs implemented will not run smoothly if there is no support from school management and administrative guidance. The aim of the research was to find out how the administration process was carried out by MIS Hanif Al Fikri. This research uses a qualitative method with a descriptive approach through observation, interviews and documentation instruments. From the research results, it was found that the administrative process carried out by MIS Hanif Al Fikri was running well. This school implements student administration, curriculum, school committee, and facilities and infrastructure effectively.